Postoperative pain after total pulpotomy and root canal treatment in mature molars according to the new and traditional classifications of pulpitis: a prospective, randomized controlled trial - Merve Sarı; Koray Yılmaz; Taha Özyürek (BMC, 2024)
Abstract Background The aim of this study was to compare postoperative pain following total pulpotomy (TP) and root canal treatment (RCT) in mature molar teeth with irreversible pulpitis. To compare the traditional pulpitis classification system with the Wolters system in evaluating postoperative pain. Methods Eighty mandibular molars with irreversible pulpitis were included and classified according to the Wolters (moderate/severe pulpitis). The teeth were randomly assigned to two groups (RCT or TP). RCT was performed following standardized protocols. TP was performed to the level of the canal orifices, and hemostasis was achieved with 2.5% sodium hypochlorite. A 3 mm layer of MTA was placed as the pulpotomy material. The teeth were restored with glass ionomer cement followed by composite. Pain scores were recorded preoperatively and, at 6, 12, 24, 48, and 72 h and 7 days after the interventions. The data were statistically analyzed using the Mann-Whitney U test, the Friedman test, the Wilcoxon signed-rank test, and the Spearman's correlation test. The significance level was set at 0.05. Results Sixty-four patients were analyzed at the one-week follow-up and all were diagnosed as irreversible pulpitis according to the AAE; 22 teeth were classified as moderate and 42 teeth were classified as severe pulpitis according to Wolters. There was no significant difference between TP and RCT in pain scores in moderate pulpitis patients (p > 0.05). There was a significant difference between TP and RCT at 24 and 72 h of severe pulpitis; higher pain scores were observed in the RCT (p < 0.05). Conclusions In patients with moderate pulpitis, the TP procedure allowed symptom relief more quickly than RCT. In patients with severe pulpitis, TP provided for significantly lower pain scores compared to RCT at both 24 and 72 h. Clinical trial registration The study was retrospectively registered with ClinicalTrials.gov (NCT05923619). Date of Registration: 06/16/23.